High Levels of BMP2 Promote Liver Cancer Growth via the Activation of Myeloid-Derived Suppressor Cells - Wu, Gui; Huang, Fei; Chen, Yaoqing; Zhuang, Yuehong; Huang, Yunpeng; Xie, Yun (Frontiers in Oncology, 2020)
Bone morphogenetic protein 2(BMP2) signaling had significant roles in diverse pathological process, such as cancer. Nevertheless, the interaction between BMP2 and carcinoma development remained largely unknown. Particularly, roles of BMP2 playing in the development of liver cancer remained controversial，and mechanisms were unclear. BMP2 with strong osteogenic potential had been manufactured into various bone materials. However, cancer risk concerns raised in recent years. Thus, we focused on analyzing the effects of exogenous BMP2 on the growth of liver cancer and the detailed mechanisms. We found that both intravenous injection of rhBMP2 and in vivo implantation of rhBMP2 materials could lead to the expansion of myeloid-derived suppressor cells (MDSCs) in peripheral blood, and subsequently enhanced the infiltration of MDSCs into tumor in vivo. Furthermore, BMP2 signaling activated MDSCs could secret IL6 to enhance cell proliferation of liver cancer cells in vitro and facilitate liver cancer growth in vivo. Our study indicated that increased concentration of BMP2 within the peripheral blood could enhance liver cancer growth via the activation of MDSCs. In this study, roles of BMP2 playing in liver cancer growth were further confirmed and the detailed mechanisms about how BMP2 enhanced the liver cancer growth were also elucidated.